Determinants of High-tech Export in CEE and CIS Countries - Drapkin, Igor M.; Gainetdinova, Anna A.; Panzabekova, Aksanat Zh. (Economy of Regions, 2021)
Any government strives to stimulate export activity in high-tech sectors of its economy. Surprisingly, there are few empirical papers on the determinants of high-tech export to date. This study analyses the economies of Central and Eastern Europe (CEE) and the Commonwealth of Independent States (CIS) due to the differences they experienced in the transition period. To this end, we used the Balassa index, which is based on the concept of revealed comparative advantages. The research examines 73 groups of products from the automotive, chemical, mechanical engineering, electronics and electrical engineering industries in 27 countries from 1995 to 2018. Principal component analysis helped generate an indicator of comparative advantage of hightech industries for each country in each year. It is revealed that CEE countries, as well as the Baltic countries, have achieved significant success in the development of high-tech sectors of the economy, while the CIS countries have shown practically no progress in this direction. The article tests hypotheses on the impact of resources, foreign trade, macroeconomy and innovation on export activity in the country. The following factors stimulate the export growth in high-tech industries of the studied countries: level of wages and resource prices, openness of the economy to foreign trade; tax rate; unemployment rate; quality of human capital. We did not find empirical evidence of the positive impact of inflation, inflows of direct foreign investment, and the level of research and development (R&D) costs on the volume of high-tech export of the examined economies.